Carpet Marketing Activities Through Direct and Indirect Marketing - Suhandyana Somantri (Lead Journal of Economy and Administration, 2022)
The purpose of this study is to find out the carpet marketing activities, to find out the obstacles that occur in carpet marketing activities and to find out what solutions the company does in overcoming the obstacles when carrying out carpet marketing activities. The research methodology used is descriptive qualitative which aims to describe the conditions and analyze carpet marketing activities. In this study, data relating to the author's study are sourced from library studies, field studies, and documentation techniques. The results of the research on carpet marketing activities are as follows: direct marketing activities carried out by the company include providing excellent service, conducting product education, recruiting distributors and providing imported products. Meanwhile, marketing activities that are carried out indirectly include utilizing the internet and social media, word of mouth promotion and utilizing applications based on the Android operating system. The constraints faced by the company are more dominant from external parties, namely related to price competition and defamation of the company's reputation through fraud cases, as well as obstacles from internal parties related to product innovation related to the designs desired by consumers. The solution that has been made by the company in overcoming the existing obstacles is by remaining consistent with the policies that have been set and always evaluating in relation to improving the quality of products and services to consumers and staying focused on doing things that can be useful for the progress of the company.